2015
DOI: 10.2527/jas.2014-8529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary lipids on sow milk composition and balance of essential fatty acids during lactation in prolific sows1

Abstract: Two studies were designed to determine the effects of supplementing diets with lipid sources of EFA (linoleic and α-linolenic acid) on sow milk composition to estimate the balance of EFA for sows nursing large litters. In Exp. 1, 30 sows, equally balanced by parity (1 and 3 to 5) and nursing 12 pigs, were fed diets supplemented with 6% animal-vegetable blend (A-V), 6% choice white grease (CWG), or a control diet without added lipid. Diets were corn-soybean meal based with 8% corn distiller dried grains with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
3
32
1
1
Order By: Relevance
“…The addition of approximately 4% of different oil sources (palm, fish, and soybean) to the diet of lactating sows improved the litter survivability and overall weight gain at weaning (Jin et al, ). Moreover, according to previous studies, the concentration of milk fat can be increased as the fat level increases in the diet, particularly that long‐chain fatty acids account as a large proportion of milk fat content in lactating sows (Rosero et al, ). Therefore, supplemental fat plus dextrose in the diet could provide considerably higher fat content in lactating sows milk.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The addition of approximately 4% of different oil sources (palm, fish, and soybean) to the diet of lactating sows improved the litter survivability and overall weight gain at weaning (Jin et al, ). Moreover, according to previous studies, the concentration of milk fat can be increased as the fat level increases in the diet, particularly that long‐chain fatty acids account as a large proportion of milk fat content in lactating sows (Rosero et al, ). Therefore, supplemental fat plus dextrose in the diet could provide considerably higher fat content in lactating sows milk.…”
Section: Discussionmentioning
confidence: 90%
“…The most noticeable benefit of dietary fat is associated with the relatively lower heat increment during digestion and metabolism processes (O'Grady, Lynch, & Kearney, ). In addition, the fat concentration in milk and colostrum can be increased by increasing dietary inclusion of fat (Rosero et al, ), which may contribute to the improvement of suckling piglets growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Miller et al and Csapó et al showed that the proportion of linoleic acids (C18:2) was reduced whereas that of palmitoleic acid (C16:1) increased during lactation [24,25]. The discrepancy between the studies can be explained by differences in animal characteristics (genotype, milk production, ability to mobilize body reserves), in animal management (amount and FA composition of the diet; Rosero et al [28]) or in the method of milk collection [5].…”
Section: Citationmentioning
confidence: 54%
“…In terms of lactation performance and consistent with the results of Mateo et al (2009), milk components such as lactose, protein and fat were not affected by the dietary treatments in this study. However, Rosero et al (2015) found greater lipid excretion in the milk of fat-supplemented sows relative to non-supplemented sows, whereas Eastwood et al (2014) found no improvement in performance when adding EPA to a sow diet. However, the increases in the milk EPA and DHA contents of sows fed the FOPF20 and FOPF40 treatments compared with the unsupplemented diet in this study are consistent with previous reports (Jensen et al, 2000;Mateo et al, 2009).…”
Section: Discussionmentioning
confidence: 90%